CONSTRUCTIVE DEALING WITH ANXIETY AND ANGER AS AN ASPECT OF THE QUALITY OF LIFE OF MATURING GIRLS WHO PRACTISE TAEKWON-DO - Wąsik, Jacek (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The quality of life, including the quality of life connected with health covers coping with difficult emotions and the ability of fulfilling aims, despite their deconstructive effects. Constructive dealing with emotions, such as anxiety and anger (i.e. that are considered to have negative character) makes a very important aspect of the quality of one’s life. The process of growing up is, to a large extent learning to cope with difficult emotions. In this work we are concentrating on one of the aspects of the quality of life connected with health-related effects of systematic physical activity performance, such as taekwon-do. One of the very important reasons of a positive influence of practising martial arts (and other forms of physical activity) on the quality of life is a beneficial impact of such an activity on a widely-understood psychophysical skills, dealing with anger and better coping with anxiety. In the light of contemporary knowledge (and old sources) taekwon-do cannot  only mean physical activity, though, undoubtedly, it is a very important, key aspect of this activity. In the paper we present the results of our own research concerning the ways of dealing with anger and anxiety by the girls practising taekwon-do (with the inclusion of the period of practise). In the light of the our research girls and women who have practised taekwon-do for over 2 years are more effective in coping with the situations of the choice between different options (to choose from) if each of them has its positive and negative consequences. Maturing girls and young women who practise taekwon-do have better abilities of constructive coping with stressful situations, including reaction for the situations causing anxiety.